Psychosocial profiles influencing healthy dietary behaviors among adolescents in Shandong Province, China: a cross-sectional study - Shi, Ya; Fu, Lin; Li, Shengping; Jiang, Ke; Shi, Zumin; Sharma, Manoj; Zhao, Yong (Frontiers in Nutrition, 2024)
Objectives We aimed to assess the influence of psychosocial profiles on dietary behaviors among school-aged adolescents in China. Methods A cross-sectional study was conducted involving 7,862 adolescents from 100 schools in Shandong, China. Psychosocial profiles and dietary behaviors were assessed using the Junior High School Students’ Psychosocial Profiles Questionnaire (JPPQ) and the Chinese Diet Quality Questionnaire (DQQ), respectively. Linear regression models were used to investigate the association between adolescents’ psychosocial profiles and dietary behaviors. Results The mean age of the participants was 13.18 ± 1.15 years; 48.5% of them were boys. The majority of participants (97.90%) were Han Chinese, and approximately half of the participants (50.90%) resided in rural areas. After adjusting for sociodemographic characteristics and family computer and Internet ownership and usage, healthy dietary behavior was positively correlated with higher psychosocial profile scores (p < 0.05). The stratified analysis results revealed that the group with the highest psychosocial profile score was associated with an increased overall global dietary reference (GDR) score in “households without a family computer and Internet” (β: 5.357, 95% Cl: 4.931–5.784, p < 0.05). Conclusion Good psychosocial profiles exhibit a positive influence on healthy dietary behaviors. Therefore, policymakers should focus on Internet usage to maximize the positive effects on global youth health behaviors.